Induction of Chronic Inflammation and Altered Levels of DNA Hydroxymethylation in Somatic and Germinal Tissues of CBA/CaJ Mice Exposed to 48Ti Ions - Rithidech, Kanokporn Noy; Jangiam, Witawat; Tungjai, Montree; Gordon, Chris; Honikel, Louise; Whorton, Elbert B. (Frontiers in Oncology, 2016)
Although the lung is one of the target organs at risk for cancer induction from exposure to heavy ions found in space, information is insufficient on cellular/molecular responses linked to increased cancer risk. Knowledge of such events may aid in the development of new preventive measures. Furthermore, although it is known that germinal cells are sensitive to X- or gamma-rays, there is little information on the effects of heavy ions on germinal cells. Our goal was to investigate in vivo effects of 1 GeV/n 48Ti ions (one of the important heavy ions found in the space environment) on somatic (lung) and germinal (testis) tissues collected at various times after a whole body irradiation of CBA/CaJ mice (0, 0.1, 0.25, or 0.5 Gy, delivered at 1 cGy/min). We hypothesized that 48Ti-ion-exposure induced damage in both tissues. Lung tissue was collected from each mouse from each treatment group at 1 week, 1 month and 6 months (mos) post-irradiation. For the testis, we collected samples at 6 months post-irradiation. Hence, only late-occurring effects of 48Ti ions in the testis were studied. There were five mice per treatment group at each harvest time. We investigated inflammatory responses after exposure to 48Ti ions by measuring the levels of activated nuclear factor kappa B and selected pro-inflammatory cytokines in both tissues of the same mouse. These measurements were coupled with the quantitation of the levels of global 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC). Our data clearly showed the induction of chronic inflammation in both tissues of exposed mice. A dose-dependent reduction in global 5hmC was found in the lung at all time-points and in testes collected at 6 mos post-irradiation. In contrast, significant increases in global 5mC were found only in lung and testes collected at 6 mos post-irradiation from mice exposed to 0.5 Gy of 1 GeV/n 48Ti ions. Overall, our data showed that 48Ti ions may create health risks in both lung and testicular tissues.